2005
DOI: 10.2344/0003-3006(2005)52[102:tmrbaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Tiagabine May Reduce Bruxism and Associated Temporomandibular Joint Pain

Abstract: Tiagabine is an anticonvulsant gamma-aminobutyric acid reuptake inhibitor commonly used as an add-on treatment of refractory partial seizures in persons over 12 years old. Four of the 5 cases reported here indicate that tiagabine might also be remarkably effective in suppressing nocturnal bruxism, trismus, and consequent morning pain in the teeth, masticatory musculature, jaw, and temporomandibular joint areas. Tiagabine has a benign adverse-effect profile, is easily tolerated, and retains effectiveness over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Nevertheless, the role of GABA in the occurrence of SB is more clear. GABA‐related drugs such as diazepam, gabapentin, tiagabine and gamma‐hydroxybutyrate have been shown to decrease the occurrence of SB, and these effects might be related to improvements of sleep and reduction of cortical arousals during sleep . This suggests that GABA may be critically important to the occurrence of SB.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the role of GABA in the occurrence of SB is more clear. GABA‐related drugs such as diazepam, gabapentin, tiagabine and gamma‐hydroxybutyrate have been shown to decrease the occurrence of SB, and these effects might be related to improvements of sleep and reduction of cortical arousals during sleep . This suggests that GABA may be critically important to the occurrence of SB.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin was successfully applied for the treatment of a 50‐year‐old man who suffered from bruxism, induced by venlafaxine (an antidepressant; see below) (136). Likewise, self‐reported bruxism was successfully managed with tiagabine in four of five cases described by Kast (137). Unfortunately, no RCT are available to assess the efficacy and safety of anticonvulsant drugs in the management of bruxism.…”
Section: Pharmacological Approachesmentioning
confidence: 91%
“…Overwhelming evidence indicates that some antiepileptic drugs, especially, gabapentin and tiagabine exert analgesic effects in both, preclinical studies on animals and clinical settings in humans. Quite recently, it has been reported that tiagabine is effective in patients with painful sensory neuropathy (Novak et al, 2001), painful tonic spasm (Solaro and Tanganelli, 2004), bruxism (Kast, 2005) and chronic pain (Todorov et al, 2005). Similarly, gabapentin is effective in suppressing and alleviating pain in postherpetic neuralgia (Garry et al, 2005; Rowbotham et al, 1998), painful diabetic neuropathy (Backonja et al, 1998), migraine (Di Trapani et al, 2000), reflex sympathetic dystrophy (Mellick and Mellick, 1997), trigeminal neuralgia (Sist et al, 1997) and neuropathic cancer pain (Caraceni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%